Synthesis of magnetic iron mannoparticles using Zea mays as a stabilizing agent - Herrera, Rosel Quispe; Nuñez, Corina Fernanda Alvarez; Quispe, Victor Sabidt Navarrete; Huamán-Romaní, Yersi-Luis; Valverde, Yolanda Paredes (International Journal of Innovative Research and Scientific Studies, 2024)
The objective of this research is to determine how to obtain magnetic iron nanoparticles through the coprecipitation technique using FeCl3 and FeSO4 as raw materials in an aqueous extract of purple corn (Zea mays L) as a stabilizing state. In recent decades, the manufacture and use of magnetic iron nanoparticles has created great importance and expectation due to their various applications in different areas, among which stands out their ability to eliminate waste that pollutes the environment. Because research design is experimental in nature due to the different samples carried out in laboratories. The selection of corn was randomized due to the ease of access to the product from a group of farmers who were previously trained to plant, cultivate, harvest, and dry purple corn. The corn antioxidants were extracted with boiling water, and the synthesis of the nanoparticles was performed by mixing FeCl3, FeSO4 in the extract solution at a temperature of 25°C for 30 min with agitation at a pH above 11 with the addition of NaOH. Characterization was performed by UV-Vis spectrophotometer. The coprecipitation method produced the magnetic iron nanoparticles using FeCl3 and FeSO4 as reagents and the aqueous extract of purple corn. The practical implications that this research will have are diverse, as theoretically it will be possible to carry out experiments with other types of corn to see the different results, as well as to use it to carry out different tests in places highly contaminated with heavy metals.